Mapping Global Theatre Histories - Pizzato, Mark (Springer, 2019)
A. Initial Questions, Terms, and Goals 1. Why study theatre history today—when information about the past is readily available on the Web and we are often more concerned about the present and future in our current “postmodern” era? It is important for artists to know the history of their art form. But are there other ways to benefit, too, from a deep yet global sense of theatricality and its many histories (or her-stories)? 2. We all engage in creative play as children, gaining a fuller sense of self (or possible selves) through imaginary interactions with others, sometimes with big people watching, providing a larger symbolic framework. Peers, parents, and other adults also model the roles we take, offering implicit scripts and explicit directions, along with costumes, props, and settings for meaningful identities. This play-acting as children and later in life involves our family, neighborhood, schools, and other communities, yet also television, movies, and interactive online media—expanding the arenas of our self and other awareness. It may also involve “deep play,” which performance theorist Richard Schechner explains as mischief, rebellion, games, and gambling with serious risks. Degrees of joyful or deep play continue from our youth into adulthood through formal theatre, sports, and videogames, on various stages with boundaries and rules.